Sequential induction of three recombination directionality factors directs assembly of tripartite integrative and conjugative elements - Haskett, T.; Terpolilli, J.; Ramachandran, V.; Verdonk, C.; Poole, P.; O Hara, G.; Ramsay, Joshua (Public Library of Science, 2018)
Tripartite integrative and conjugative elements (ICE3) are a novel form of ICE that exist as three separate DNA regions integrated within the genomes of Mesorhizobium spp. Prior to conjugative transfer the three ICE3 regions of M. ciceri WSM1271 ICEMcSym1271 combine and excise to form a single circular element. This assembly requires three coordinated recombination events involving three site-specific recombinases IntS, IntG and IntM. Here, we demonstrate that three excisionases–or recombination directionality factors—RdfS, RdfG and RdfM are required for ICE3 excision. Transcriptome sequencing revealed that expression of ICE3 transfer and conjugation genes was induced by quorum sensing. Quorum sensing activated expression of rdfS, and in turn RdfS stimulated transcription of both rdfG and rdfM. Therefore, RdfS acts as a “master controller” of ICE3 assembly and excision. The dependence of all three excisive reactions on RdfS ensures that ICE3 excision occurs via a stepwise sequence of recombination events that avoids splitting the chromosome into a non-viable configuration. These discoveries expose a surprisingly simple control system guiding molecular assembly of these novel and complex mobile genetic elements and highlight the diverse and critical functions of excisionase proteins in control of horizontal gene transfer.